توزيف منصة إديوكابلاي (Educaplay) في تعليم الأصوات والمفردات العربية للمستوى المبتدئ - Adzrah Dwi Sunarty Abas; Mu Ida Nur Fadhilah; Adam Nadzirul Wuqu`; Miftahul Huda ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2026)
The integration of digital technology in education has created new opportunities to improve Arabic language learning, particularly in teaching phonetics and vocabulary at the beginner level. These two components are fundamental to the development of listening, speaking, reading, and writing skills. This study aims to describe the utilization of the Educaplay platform in teaching Arabic phonetics and vocabulary and to identify its advantages and limitations in Arabic language learning. This research employed a library research method with a qualitative descriptive approach. Data were collected from books, scientific journals, conference proceedings, and official Educaplay documentation, and analyzed using content analysis techniques. The findings indicate that Educaplay can support phonetics learning through interactive activities that help learners recognize, distinguish, and pronounce Arabic sounds correctly. In vocabulary learning, features such as Matching Pairs, Froggy Jumps, and Memory facilitate vocabulary acquisition, retention, and recall. Furthermore, Educaplay enhances learning motivation, participation, and independent learning. However, its implementation requires internet access, digital devices, and adequate technological skills. Therefore, Educaplay can be considered an effective digital learning platform for supporting beginner-level Arabic phonetics and vocabulary instruction.